HUBUNGAN NALAR BAYANI, NALAR BURHANI, DAN NALAR IRFANI DALAM INTEGRASI INTERKONEKSI KEILMUWAN AMIN ABDULLAH - Ulviana (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The concept of integration-interconnection is no longer unfamiliar, and it has even become an ideology in Islamic Higher Education Institutions (PTKIN). In this integration, Amin Abdullah employs Al-Jabiri’s epistemology, which consists of three modes of reasoning: bayani, burhani, and irfani. In Bayani reasoning, rationality is used merely as a tool to justify texts, while in Burhani reasoning, rational thought is applied to seek objective truth. The source of the texts in Burhani's reasoning is reality. Additionally, the thinking method that connects the two is intuitive reasoning. Intuitive reasoning draws its source from experiences and spiritual insights, which are intersubjective. To delve deeper into Amin Abdullah’s concept of integration-interconnection, an understanding of these three modes of reasoning is essential. Therefore, this article will explore Bayani, Burhani, and Irfani's reasoning in more detail. This research is a literature review, gathering data from primary and secondary sources. The primary sources are literature that discusses M. Amin Abdullah’s integrative-interconnective concept, while the secondary sources are complementary scientific literature. The result of this research is an explanation of the relationship between bayani, Burhani, and Irfani reasoning within the integrative-interconnective knowledge concept of Amin Abdullah.